Drinking in denial: a cross-sectional analysis of national survey data in Ireland to measure drinkers’ awareness of their alcohol use - Mongan, Deirdre; Millar, Sean R; O'Dwyer, Claire; Long, Jean; Galvin, Brian (BMJ open, 2020)
ObjectivesIreland has high per capita alcohol consumption and also has high levels of problematic drinking patterns. While it is accepted that patterns of alcohol consumption in Ireland are a cause for concern, it is not clear if Irish people are actually aware of the extent of their hazardous or harmful pattern of drinking. The aim of this study was to determine awareness of drinking pattern in an Irish population using a representative random sample and to identify characteristics associated with self-awareness of hazardous or harmful drinking.MethodsWe analysed data from Ireland’s 2014/2015 Drug Prevalence Survey which recruited a stratified clustered sample of 7005 individuals aged 15 years and over living in private households. Logistic regression analysis was used to determine characteristics associated with self-awareness of hazardous or harmful drinking.ResultsAlmost one half of drinkers had a hazardous or harmful pattern of drinking; 38% engaged in monthly risky single occasion drinking (RSOD) and 10.5% met Diagnostic and Statistical Manual version IV (DSM-IV) criteria for alcohol dependence. Of the 2420 respondents who had a hazardous or harmful pattern of drinking, 67% were unaware of this and misclassified themselves as being either a light or moderate drinker who did not engage in RSOD. An adjusted logistic regression model identified that hazardous and harmful drinkers were more likely to be aware of their drinking pattern if they had completed third level education (OR=1.80, 95% CI: 1.30 to 2.49) while older drinkers (aged 65 and over) were less likely to be aware of their drinking pattern (OR=0.30, 95% CI: 0.14 to 0.65). Subjects who engaged in risk taking behaviours such as illicit drug use and gambling were also significantly more likely to be aware of their drinking pattern.ConclusionsThe results of this study suggest that patterns of alcohol use in Ireland are problematic. Older respondents and those with lower educational attainment are less likely to be aware of their hazardous or harmful drinking pattern. There is also a population of younger, more-educated drinkers who engage in potentially risk-taking behaviours and these subjects are aware of their harmful drinking pattern. Initiatives to reduce overall alcohol consumption and raise awareness around drinking patterns are required.